Evaluation of enzyme-linked immunosorbent assay (ELISA) and enzyme-linked immunoelectrotransfer blot (EITB) for immunodiagnosis of hydatid diseases in sheep - Simsek, S; Koroglu, E (Elsevier Science Bv, 2004)
This study was undertaken to investigate antigenic characteristics of hydatid cyst fluid in sheep by SDS-PAGE method, to evaluate sensitivity and specificity of Enzyme-linked immunosorbent assay (ELISA) and Enzyme-linked immunoelectrotransfer blot (EITB) assay for diagnosis of sheep hydatidosis, and to determine seroprevalance of hydatidosis in sheep population in Elazig, Turkey. SDS-PAGE analysis of hydatid cyst fluids indicated that 6 specific-protein bands were detected at Molecular weights of 29, 45, 58, 68, 98 and 116 kDa. EITB analysis showed presence of 29, 38,42, 58, 62, 68, 98, 116, 120, 150 and 205 kDa bands in positive sheep sera, while 38, 58, 62, 68, 116 and 205 kDa bands were detected in negative sheep sera. Therefore, it was concluded that the 116 kDa band was specific for diagnosis of sheep hydatid disease by EITB assay. Sensitivity and specificity of EITB assay were determined as 88% and 84%, respectively, whereas corresponding rates for ELISA were 60% and 94%, respectively. Sensitivity of ELISA was 47.3% in hepatic cysts, 60% in pulmonary cysts, 69.2% in hepato-pulmonar cysts. Sensitivity ratios of ELISA were 67.8%, 75%, and 38.4% for fertile, sterile, and under-growth cysts, respectively. Sensitivity of EITB was found 84.2% in hepatic cysts, 80% in pulmonary cysts, and 92.3% in hepato-pulmonar cysts. Corresponding ratios for sensitivity of EITB for fertile, sterile, calcified, and under growth cysts were 92.8%, 75%, 100%, and 84.6%, respectively. In addition, seroprevalance of hydatidosis in sheep was found as 62% by ELISA and 66.4% by EITB in Elazig, Turkey and seroprevalance increased by age. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: hydatid cyst; sheep; SDS-PAGE; EITB; ELISA; sensitivity